A consistent taxonomic treatment for dimorphic variation in New Zealand Adiantum species. Issue 4 (2nd October 2019) - Brownsey, Patrick J.; Shepherd, Lara D.; Perrie, Leon R.
ABSTRACT: Recent treatments have recognised seven species indigenous to New Zealand in the fern genus Adiantum. Most of these species display dimorphism with respect to the presence or absence of hairs on the abaxial pinna surfaces, or the nature of the hairs themselves. Taxonomic treatment of these dimorphisms has not been consistent, with variation sometimes treated at the specific or varietal levels, or not recognised at all. Morphological variation in the pinna hair characters of all indigenous species is examined here, and the taxonomic significance of the variation reassessed to bring a consistent approach to classification in New Zealand Adiantum . It is concluded that glabrous and hairy variants should not be given taxonomic recognition, but should be considered dimorphisms within those species that are distinguished on the basis of other morphological characters. As a consequence, A. viridescens is reduced to synonymy with A. fulvum, since the two cannot be distinguished by any character other than the glabrous or hairy nature of the pinnae.